PENERAPAN PRINSIP CONTEXTUAL TEACHING & LEARNING BERBANTUAN GEOGEBRA PADA MATERI SISTEM KOORDINAT - Cahya Ercy Dwiputri; Nyimas Aisyah; Indaryanti; Zuli Nuraeni; Novika Sukmaningthias (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2021)
The learning process that is carried out optimally is a learning process that involves students actively. One of the learning approaches that can actively involve students is the contextual approach or Contextual Teaching & Learning (CTL). This qualitative research aims to determine students' activities during the implementation of CTL principles with GeoGebra assisted in a cartesius coordinate system at SMP Negeri 9 Palembang. The subjects were four students of VIII.3 SMP Negeri 9 Palembang. Data was collected online using observation sheets, questionnaires, interviews, & analyzed descriptively. From this research, it is concluded that the principles of CTL that appear in GeoGebra-assisted mathematics learning were constructivism, inquiry, modeling, authentic assessment, & learning community. Then the CTL principles that rarely appear during learning were questioning, & reflection.